The Sister Chromatid Division of the Heteromorphic Sex Chromosomes in Silene Species and Their Transmissibility towards the Mitosis - Bačovský, Václav; Janíček, Tomáš; Hobza, Roman (International journal of molecular sciences, 2022)
Young sex chromosomes possess unique and ongoing dynamics that allow us to understand processes that have an impact on their evolution and divergence. The genus Silene includes species with evolutionarily young sex chromosomes, and two species of section Melandrium, namely Silene latifolia (24, XY) and Silene dioica (24, XY), are well-established models of sex chromosome evolution, Y chromosome degeneration, and sex determination. In both species, the X and Y chromosomes are strongly heteromorphic and differ in the genomic composition compared to the autosomes. It is generally accepted that for proper cell division, the longest chromosomal arm must not exceed half of the average length of the spindle axis at telophase. Yet, it is not clear what are the dynamics between males and females during mitosis and how the cell compensates for the presence of the large Y chromosome in one sex. Using hydroxyurea cell synchronization and 2D/3D microscopy, we determined the position of the sex chromosomes during the mitotic cell cycle and determined the upper limit for the expansion of sex chromosome non-recombining region. Using 3D specimen preparations, we found that the velocity of the large chromosomes is compensated by the distant positioning from the central interpolar axis, confirming previous mathematical modulations.
Keywords: molekulární evoluce; central interpolar axis; hybridizace in situ fluorescenční; Sex Chromosomes; mitóza; Microscopy, Confocal; pohlavní chromozomy; hydroxymočovina; Chromosomes, Plant; konfokální mikroskopie; In Situ Hybridization, Fluorescence; Mitosis; Chromatids; chromatidy; chromozomy rostlin; sex chromosomes; Silene; chromosome velocity; sister chromatid division; Hydroxyurea; Evolution, Molecular